European Parliament election - TUC poster, 1989 (London, 1989)
1989 1980-95 "European Parliament election - TUC poster, 1989" [BW0145], 1989, Trades Union Congress The TUC encouraged people to vote in the election to ensure that the completion of the Single European Market in 1992 became an opportunity to give the European Community a social dimension, including the establishment of a platform of guaranteed social rights.